Arginine-mediated regulation of an argininosuccinate synthetase minigene in normal and canavanine-resistant human cells. - Jackson, M J (1986)
Regulation of argininosuccinate synthetase (AS) was studied by using minigenes containing 3 kilobases of DNA upstream from the TATAA box and 9 kilobases downstream (including the first four exons of the AS gene) ligated to either the cDNA for AS or to the chloramphenicol acetyltransferase (CAT) gene. Unlike the endogenous AS gene, expression of the CAT minigene was not elevated in Canr1 cells, which overproduce AS compared with parental RPMI-2650 cells. Expression of the CAT minigene in both stable and transient analyses was four- to five-fold higher in RPMI-2650 cells grown in citrulline medium than in cells grown in arginine medium. Although endogenous AS activity is not subject to metabolite regulation in Canr1 cells and expression of the CAT minigene in Canr1 cells was not increased when cells were grown in citrulline medium, expression of the CAT minigene was 10- to 22-fold greater when intracellular arginine pools were depleted by transient starvation for arginine and citrulline.